Application Of Ways To Increase Efficiency In Learning The Russian Language (Texas Journal of Multidisciplinary Studies, 2024)
The relevance of this article is determined by the need to keep up with the times when teaching students. Lessons taught by the teacher must meet modern educational standards. These standards have undergone significant changes in recent years. And since methodology is a pedagogical science that develops issues of the content of the principles and methods of teaching a specific subject, then all issues of changing standards are addressed primarily to it. The main issues in modern methodology are the formation of interest in the Russian language and the improvement of the methodology itself. The purpose of the article is to identify the most effective ways to increase the effectiveness of the Russian language lessons